The paradox of predictivism - Barnes, Eric Christian . (Cambridge : Cambridge University Press, 2011)
In The Paradox of Predictivism, Eric Barnes contends that the successful prediction of evidence serves as a testament to the overall credibility of the predictor, unlike evidence that is used to support a theory. He illustrates his argument with a significant example from nineteenth-century chemistry: Mendeleev's Periodic Law and its successful predictions of the existence of various elements.
CHAPTER 1 The paradox of predictivism; CHAPTER 2 Epistemic pluralism; CHAPTER 3 Predictivism and the Periodic Table of the Elements; CHAPTER 4 Miracle arguments and the demise of strong predictivism; CHAPTER 5 The predicting community; CHAPTER 6 Back to epistemic pluralism; CHAPTER 7 Postlude on old evidence; CHAPTER 8 A paradox resolved.
Includes bibliographical references and index.
Keywords: Philosophy; Probability; Science - Philosophy